Measuring the effects of mergers and acquisitions on the economic performance of real estate developers - Jin, Zhigang; Xia, Bo; Li, Vera; Li, Heng; Skitmore, Martin (International Journal of Strategic Property Management, 2015)
Real estate developers in China are using mergers and acquisitions (M&As) to ensure their survival and competitiveness. However, no suitable method is yet available to assess whether such M&As provide enhanced value for those involved. Using a hybrid method of data envelopment analysis (DEA) and Malmquist total factor productivity (TFP) indices, this paper evaluates the short and medium term effects of M&As on acquirers’ economic performance with a set of 32 M&A cases occurring during 2000–2011 in China. The results of the analysis show that M&As generally have a positive effect on acquirers’ economic performance. Acquisitions on average experienced a steady growth in developer Malmquist TFP, a more progressive adoption of technology immediately after acquisition, a slight short-term decrease in technical efficiency after acquisition but followed by a marked increase in the longer term once the integration and synergy benefits were realised. However, there is no evidence to show whether developers achieved any short or long term scale efficiency improvements after M&A. The findings of this study provide useful insights on developer M&A performance from an efficiency and productivity perspective.First Publish Online: 23 Dec 2015